APRESENTAÇÃO DOS CADERNOS DO IL 56 - Silva, Silvana; Solé, Alessandra Santos; Ulrich, Camila Witt; Heineck, Débora; Monteiro, Evandro Oliveira; Aresi, Fábio; Paz, Juliana Ferreira; Habel, Jussara Maria; de Borba, Laura Campos; Passini, Michele Teixeira; de Oliveira, Samuel Gomes; Hoff, Sara Luiza; et al. (Cadernos do IL, 2018)
APRESENTAÇÃO DOS CADERNOS DO IL 56